A comparison of the antiplatelet effects of prasugrel and high-dose clopidogrel as assessed by VASP-phosphorylation and light transmission aggregometry - Jakubowski, Joseph A; Payne, Christopher D; Li, Ying G; Farid, Nagy A; Brandt, John T; Small, David S; Salazar, Daniel E; Winters, Kenneth J (Thrombosis and Haemostasis, 2008)
Platelet inhibition as measured by vasodilator-stimulated phosphoprotein (VASP) and light transmission aggregometry (LTA) have shown concordance following dosing of clopidogrel. No reports have directly compared theVASP assay and LTA at the levels of P2Y12 blockade after loading doses (LDs) of prasugrel or high dose clopidogrel (600 and 900 mg).The aim was to compare theVASP assay and LTA during the loading dose phase of a comparative study of prasugrel and clopidogrel. Prasugrel 60 mg LD/10 mg maintenance dose (MD) and clopidogrel 300 mg/75 mg and 600 mg/75 mg LD/MD regimens were compared in a 3-way crossover study in 41 healthy, aspirin-free subjects. Each LD was followed by seven daily MDs and a 14-day washout period. P2Y12 receptor blockade was estimated using theVASP assay, expressed as platelet reactivity index (VASP-PRI). Platelet aggregation was assessed by light transmission aggregometry (20 and 5 μM ADP).Twenty-four hoursafter prasgurel 60 mg or clopidogrel 300 mg and 600 mg, respectively, VASP-PRI decreased from ∼80% to 8.9%, 54.7%, and 39.0 %, and maximal platelet aggregation (MPA) decreased from ∼79% to 10.8%, 42.7%, and 31.2%, with an overall VASP:MPA correlation of 0.88 (p<0.01). VASP assay responses after the clopidogrel LDs showed a wider range of values (300 mg: 0–93%; 600 mg: 0–80%) than prasugrel (0–13%); MPA responses followed a similar trend. Pearson’s correlation suggested a strong agreement between VASP and LTA (20 μM ADP) for MPA (r=0.86, p<0.0001).VASP and LTA demonstrated concordance across the response range of P2Y12 receptor blockade following thienopyridine LDs.
Keywords: Clopidogrel; prasugrel; P2Y12; thienopyridine; VASP